Big Data Made Easy A Working Guide to the Complete Hadoop Toolset - Frampton, Michael (Springer, 2015)
Relational database systems encounter data-quality problems, and they use data-quality rules to solve those problems. Hadoop Hive has the potential to hold an extremely large amount of data—a great deal larger than traditional relational database systems and at a lower unit cost. As the data volume rises, however, so does the potential for encountering data-quality issues...